Evaluasi Strategi Penetapan Tarif Untuk Meningkatkan Pendapatan Kapal Penumpang - Ziqra Maulana Zulmarjon; Siti Sahara (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Passenger ships play an important role in sea transportation and island crossings. Effective tariff setting in passenger ship operations can influence revenue, profits and customer satisfaction. This research aims to evaluate the tariff setting strategies implemented by shipping companies in the context of their passenger ships Evaluation of tariff setting strategies to increase passenger ship revenues can be carried out using ship operational cost analysis, unit rate analysis and fare revenue analysis which greatly influence the level of public service and the current passenger ship service fee is the tariff during the pilot route since the fuel price increase policy was issued. Research can determine the minimum tariff that can cover ship operational costs and the tariff that can be paid by service users.